Gestión Productiva De Los Pequeños Agricultores De Ciclo Corto Y El Desarrollo Socioeconòmico De Las Familias Del Cantón Montalvo, Provincia De Los Rìos - Rivadeneira Avilez, Gabriela (2015)
The productive activity of small farmers engaged in cultivation of short cycle in any sector of the country, contributing to the socioeconomic development of the community and Ecuador, so this research developed in the canton Montalvo, is of utmost importance because will determine the family's economic and society montalvina contribution. In developing the study has identified the problems through observation, which allowed them to determine the purpose of the investigation, considering as an important part of the people doing this productive activity in the canton Montalvo, determining that the inhabitants of Montalvo 90% are engaged in agricultural activity, especially short cycle, so this activity contributes to the economic development of the canton, province and country. It has been defined that a high percentage of farmers have no knowledge of administrative management, making many of the decisions are not appropriate, nor is determined correctly the economic result of productive activity, which is You need this knowledge that will allow increasing productivity for the benefit of farmers and therefore will produce a monetary circulation in Canton, reactivating complementary activities in the field of trade and services.